La protección del menor en los casos de gestación por sustitución: análisis de diversos supuestos prácticos - Francisca Ramón Fernández (Revista Sobre la Infancia y la Adolescencia, 2014)
This paper discusses an issue of great importance in family law, as in the case of surrogacy and child protection. Many times we read news related to filiation through the related subrogation familiar characters. We propose, therefore, to study through various practical cases in which the court has ruled and the Directorate General of Registries and Notaries, the main conflicts arising from the registration of children born out of our country and the recognition of parenthood, from the position of the protection and best interests of the child. We intend to see the position taken by the legislation, doctrine and jurisprudence in a case marked by a law which is scheduled to change in the future.